LATE for the Meeting: Gender, Peer Advising, and College Success - Jimmy R. Ellis; Seth Gershenson (Institute for the Study of Labor (IZA), 2016)
Many male and first-generation college goers struggle in their first year of postsecondary education. Mentoring programs have been touted as a potential solution to help such students acclimate to college life, yet causal evidence on the impact of such programs, and the factors that influence participation in them, is scant. This study leverages a natural experiment in which peer advisors (PA) were quasi-randomly assigned to first-year university students to show that: (i) male students were significantly more likely to voluntarily meet their assigned PA when the PA was also male and (ii) these compliers were significantly more likely to persist into the second year of postsecondary schooling. We find no effect of being assigned to a same-sex PA on female students' use of the PA program, nor do we find any evidence that the PA program affected subsequent academic performance (GPAs).
Keywords: I21; I23; I28; 330; higher education; peer advising; mentoring; gender gap; retention; demographic mismatch